Clinical efficacy study of the lateral parapatellar approach combined with the “Hedgehog” technique in treating complex comminuted patellar fractures - Ma, Teng; Chao, Lili; Wei, Daihao (Frontiers in Surgery, 2025)
ObjectiveThe present study aimed to investigate the efficacy of the lateral parapatellar approach combined with multiple Kirschner wire tension bands (“Hedgehog” technique) in the treatment of complex comminuted patellar fractures, improving surgical outcomes, and promoting early recovery of knee joint function.MethodsThis study adopted a retrospective design. Based on the inclusion and exclusion criteria, patients with complex comminuted patellar fractures admitted to the hospital from January 2018 to January 2024 were enrolled. Among them, 21 patients in Group A were treated via the lateral parapatellar approach combined with multiple Kirschner wire tension bands and Ethibond suture fixation, whereas 24 patients in Group B underwent conventional midline anterior patellar approach combined with Kirschner wire tension band fixation. The two groups were compared and analyzed in terms of incision length, intraoperative blood loss, operation time, reduction quality, VAS score, postoperative complications, Böstman score, initiation time of postoperative knee functional exercises and the last follow-up KOOS score.ResultsAll patients had complete follow-up data, with a mean follow-up duration of 18 months, and there were no statistically significant differences in baseline characteristics between the two groups. Compared with Group B, Group A had significantly better outcomes in terms of operation time, reduction quality, VAS score (3 days postoperatively), incidence of postoperative complications (scarring), Böstman score (3, 6, and 12 months postoperatively), fracture healing time, initiation time of knee functional exercises and KOOS score (P < 0.05). No statistically significant differences were observed between the two groups in terms of incision length, intraoperative blood loss, VAS score (1 day postoperatively), or postoperative complications (pin migration, irritation, and infection) (P > 0.05).ConclusionIn the surgical management of complex comminuted patellar fractures, the lateral parapatellar approach allows for precise reduction of fracture fragments under direct visualization, achieving anatomical reduction with reliable fixation. This approach facilitates early functional exercises, accelerates rehabilitation, and achieves favorable clinical outcomes while avoiding patellectomy, and thus may represent a valuable alternative technique. The simple and cost-effective internal fixation technique using a Kirschner wire tension band combined with Ethibond suture remains vigorously viable in the era of rapidly advancing orthopaedic treatment technologies.